Osteossarcoma mandibular em gato: Relato de Caso - Costa Neto, J. M. (2011)
The primary malignant bone tumors are uncommon in cats. Osteosarcoma is the most frequently observed in old animals. This tumors affects the appendicular skeleton, however the axial skeleton is also affected, but the bones of the head and pelvis frequent sites of injury. This paper reports a case of a cat with a history of progressive swelling in the left mandible, with follow-up period of four months. The presumptive diagnosis of osteopathy, signed by clinical and radiographic observations were confirmed by histopathology and there it is moderately productive osteoblastic osteosarcoma.